Mutu Fisiologis Benih Kedelai Hitam Hasil Iradiasi Sinar Gamma Selama Periode Simpan - Tri Yulita Dewi; Siti Novridha Andini; Onny Chrisna Pandu Pradana; Ratna Dewi (Planta Simbiosa, 2023)
Soybean seeds are stored before being planted in the field, during this storage period the seeds can experience deterioration, if not stored in appropriate environmental conditions, seed deterioration will occur more quickly and can reduce the physiological quality of the seeds. The research aims to determine the physiological quality of gamma-ray irradiated black soybean seeds during the storage period. This study used a non-factorial completely randomized design , with control/no irradiation treatment of 0 Gy (R0) and 5 doses of gamma irradiation, including: 50 Gy (R1), 100 Gy (R2), 150 Gy (R3), 200 Gy (R4), 250 Gy (R5), each treatment was repeated four times. The variables observed were electrical conductivity test, seed germination, growing district, germination height, vigor index, and growing simultaneity. The results showed that the higher the dose of irradiation, the lower the percentage of seed germination, and the lower the physiological quality. Key word: Seed storage, Black soybean, Irradiation